Quality Affordable Housing: A Theoretical Framework for Planning and Design of Quality Housing - Sultan Sidi, Noor Sharipah (Journal of Techno-Social, 2010)
The provision of adequate, good or quality housing for the population has always been a major challenge and task for most nations in the world particularly the developing countries. As such various measures have been undertaken towards this end. However, the major constraint or problem in this respect has always been in defining the criteria for quality housing and establishing the standards of quality housing particularly with respect to the parameters in the determination of quality as some of the parameters are subjective and contextual such as psychological, cultural and environmental aspects. This paper is aimed at discussing the concept of quality housing and establishing the parameters and theoretical framework which can be used by researchers, town planners, architects, policy makers and others in the formulation of criteria / guidelines for the planning and design of quality housing.